Metabolic dysfunction in OSA: Is there something new under the sun? - Almendros Isaac; Basoglu Özen K; Conde Silvia V; Liguori Claudio; Saaresranta Tarja (WILEY, 2022)
The growing number of patients with obstructive sleep apnea is challenging healthcare systems worldwide. Obstructive sleep apnea is characterized by chronic intermittent hypoxaemia, episodes of apnea and hypopnea, and fragmented sleep. Cardiovascular and metabolic diseases are common in obstructive sleep apnea, also in lean patients. Further, comorbidity burden is not unambiguously linked to the severity of obstructive sleep apnea. There is a growing body of evidence revealing diverse functions beyond the conventional tasks of different organs such as carotid body and gut microbiota. Chronic intermittent hypoxia and sleep loss due to sleep fragmentation are associated with insulin resistance. Indeed, carotid body is a multi-sensor organ not sensoring only hypoxia and hypercapnia but also acting as a metabolic sensor. The emerging evidence shows that obstructive sleep apnea and particularly chronic intermittent hypoxia is associated with non-alcoholic fatty liver disease. Gut dysbiosis seems to be an important factor in the pathophysiology of obstructive sleep apnea and its consequences. The impact of sleep fragmentation and intermittent hypoxia on the development of metabolic syndrome may be mediated via altered gut microbiota. Circadian misalignment seems to have an impact on the cardiometabolic risk in obstructive sleep apnea. Dysfunction of cerebral metabolism is also related to hypoxia and sleep fragmentation. Therefore, obstructive sleep apnea may alter cerebral metabolism and predispose to neurocognitive impairment. Moreover, recent data show that obstructive sleep apnea independently predicts impaired lipid levels. This mini-review will provide novel insights into the mechanisms of metabolic dysfunction in obstructive sleep apnea combining recent evidence from basic, translational and clinical research, and discuss the impact of positive airway pressure treatment on metabolic disorders.